Investigation of electrodeposition of Ni-Co-Fe-Zn alloys in DMSO with MHD effect - Ebadi, M.; Leng, S.Y.; Mahmoudian, M.R.; Alias, Y.; Basirun, Wan Jefrey (Elsevier, 2012)
This paper reports the magneto-electrodeposition of the Ni-Co-Fe-Zn alloys by chronoamperometry in Dimethyl Sulfoxide solvent in the presence and absence of a Permanent Parallel Magnetic Field (PPMF) to the cathode surface. It was found that the deposition current in the presence of PPMF (9 T) was enhanced compared to the absence of PPMF. The current enhancement percentage (η%) was increased when deposited in the presence of PPMF (η% = 2 ± 0.07%, 15.78 ± 0.93% and 21.6 ± 1.04%) for 1 h at - 1.10, - 1.20 and - 1.30 V respectively. Deposition at higher potentials in the presence of PPMF was also found to increase the deposition efficiency. The Composition Reference Line for Ni was calculated to be around 25%, although the noble metals (i.e., Ni, Co) showed anomalous deposition behavior in the presence of the less noble elements like Zn and Fe. The nucleation and growth were also investigated during the electrodeposition process. It was shown that nucleation and diffusion coefficients were promoted when using PPMF and increasing of applied potential. The corrosion behavior of the alloy surface was examined by the Open Circuit Potential and Electrochemical Impedance Spectroscopy. The results showed that the corrosion resistance increased with the increase of content of more noble metals. © 2012 Elsevier Inc.